2005
DOI: 10.1002/bem.20137
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 50 Hz electric field on plasma lipid peroxide level and antioxidant activity in rats

Abstract: The effects of exposure to extremely low frequency electric fields (ELF EFs) on plasma lipid peroxide levels and antioxidant activity (AOA) in Sprague-Dawley rats were studied. The test was based on comparisons among rats treated with a combination of the oxidizing agent, 2,2'-azobis(2-aminopropane) dihydrochloride (AAPH) and 50 Hz EF of 17.5 kV/m intensity for 15 min per day for 7 days, AAPH alone, EF alone or no treatment. EF significantly decreased the plasma peroxide level in rats treated with AAPH, simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 24 publications
1
37
0
1
Order By: Relevance
“…Under our experimental conditions it was also possible to note a significant increase of ROS production in two tested cell lines even with a different qualitative and quantitative timecourse. It should be mentioned that "in vivo" experiments in literature also seem to confirm that chronic exposure to ELF-EMF is able to generate a stress oxidative status [32][33][34]. The "in vitro" experiments reported here, as well as the results derived from "in vivo" techniques [13,22,24,25,28,35,36] in mice, show that the presence of ELF-EMF can induce a variable and specie-specific alteration of the stress oxidative pathway.…”
Section: Discussionsupporting
confidence: 79%
“…Under our experimental conditions it was also possible to note a significant increase of ROS production in two tested cell lines even with a different qualitative and quantitative timecourse. It should be mentioned that "in vivo" experiments in literature also seem to confirm that chronic exposure to ELF-EMF is able to generate a stress oxidative status [32][33][34]. The "in vitro" experiments reported here, as well as the results derived from "in vivo" techniques [13,22,24,25,28,35,36] in mice, show that the presence of ELF-EMF can induce a variable and specie-specific alteration of the stress oxidative pathway.…”
Section: Discussionsupporting
confidence: 79%
“…This may be due to interaction with moving charges and enzymes activities rates in cell-free systems increasing transcript levels for specific genes, or interacts directly with electrons in DNA to affect protein biosynthesis [5,49]. Exposure to a low magnetic field decreased plasma peroxide level in stressed rats [56]. It is possible that EMF can ameliorate the deleterious effects of Free radicals by decreasing the chemical reactions that caused damage to DNA, proteins and lipids [2].…”
Section: Effect Of Magnetic Water On Biochemical Parametersmentioning
confidence: 99%
“…These include effects on energy metabolism, specifically glycolysis, in restriction stressed rats [17]. In addition, we have also found that lipid peroxide level increase with the oxidizing agent was reduced by EF [19]. Therefore, we hypothesized that an EF might have an effect on the energy metabolism of organisms undergoing stress.…”
Section: Discussionmentioning
confidence: 94%